2012
DOI: 10.4236/fns.2012.35090
|View full text |Cite
|
Sign up to set email alerts
|

Amylolytic Activity in Selected Sweetpotato (<i>Ipomoea batatas</i> Lam) Varieties during Development and in Storage

Abstract: Sweetpotato varieties (five) were investigated for changes in <i>α</i>- and <i>β</i>-amylase activities during root development and on subjection of harvested roots to different postharvest handling and storage conditions. Changes in <i>α</i>- and <i>β</i>-amylase activities in development were monitored from 10 weeks after planting. At physiological maturity, sweetpotato roots were harvested and subjected to various conditions: freshly harvested roots and cured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 24 publications
7
24
0
Order By: Relevance
“…The results from this study, showing very minimal changes in soluble solids at temperature ranges from 70 to 80°C, are in agreement with Nabubuya, Namuteb, Byaruhanga, Narvhus, Stenstrøm, et al. () who observed that the activity of amylases in sweet potato flours is highest at around 80°C, beyond which temperature the enzymes are denatured.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…The results from this study, showing very minimal changes in soluble solids at temperature ranges from 70 to 80°C, are in agreement with Nabubuya, Namuteb, Byaruhanga, Narvhus, Stenstrøm, et al. () who observed that the activity of amylases in sweet potato flours is highest at around 80°C, beyond which temperature the enzymes are denatured.…”
Section: Resultssupporting
confidence: 92%
“…Nabubuya, Namuteb, Byaruhanga, Narvhus, Stenstrøm, et al. () in a study comparing fresh and stored sweet potato roots also observed that the activity of endogenous amylases was higher in stored than in fresh roots. This implies that pastes obtained by use of flours from fresh sweet potato roots are more firm and elastic in nature, unlike those prepared from flours obtained from stored roots, which are more viscous in nature.…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations